Graphs and the Prime Spectrum of Unitary Commutative Rings (European Journal of Pure and Applied Mathematics, 2023)
In this paper, we study the relationships between graphs and the prime spectrum of unitary commutative rings. It is shown that a graph G equipped with the G-right topology satisfies some spectral properties. In particular we give a necessarily and sufficient condition to obtain a spectral graph.
Keywords: prime spectrum; graph; topology; quasi-homeomorphism